Illustrated Workflow for Automatic Data Reduction and Quantification of X-ray Computed Tomography Images of Sedimentary Cores - Philippe J. Gaillot; Mathieu J. Duchesne; Peter Blum (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 2, 2023)
The developed workflow reduces information contained in 3-Dimensional single energy X-ray computed tomography (XR-CT) images of sedimentary rocks into sub-mm scale resolution core scalar and core image logs. The resulting log views provide a quantitative and compact (data volume reduction of \(\) 90%) description of the XR-CT images easing core-log-seismic integration efforts. Density-related outputs are calibrated using automatic integration with continuous digital visual core description (VCD) and discrete moisture and density (MAD) property index measurements of selected samples. Following the conversion of the X-ray attenuation coefficients into density values based on lithology, quantitative presentations include (1) histogram of the distribution of density values and its related statistical parameters, (2) radial and angular distributions of core density values, (3) volume, average density and mass contributions of three core fractions defined by density thresholds corresponding to voids or vugs (VV, density \(\) \(\) 1 g.cm-3), and a break in the histogram of distribution of the density values showing the limit between the damaged (DM) and non-damaged (ND) fractions of the core material, and so, (4) provide a sub-mm scale bulk density core log free of any drilling disturbance. The method is demonstrated using data from the 365 m deep Hole C9001C drilled off-shore Shimokita (northeast coast of Honshu, Japan) and early stage of the Nankai Trough Seismological zone (NanTroSEIZE, Center for Deep Earth Exploration-Jamstec, International Ocean Discovery Program). The outputs can be used for a variety of purposes, such as (1) derivation of sub-mm scale porosity core log, (2) correction of volume sensitive measurements in case of poor core quality and partially filled core liner, and (3) seismic modeling and well ties.